Across the river and into the trees: Earthworms in a Central European Floodplain National Park - Dmytro Monoshyn; Marion Mittmannsgruber; Edith Gruber; Elisabeth Wiedenegger; Barbara Simon; Csaba Csuzdi; Johann G. Zaller (Applied Soil Ecology, 2026)

Life, death, and microbes: The role of land use and environmental gradients in soil microbial carbon dynamics - Dmytro Monoshyn; Marion Mittmannsgruber; Rajasekaran Murugan; Erich Inselsbacher; Edith Gruber; Elisabeth Wiedenegger; Johann G. Zaller (Applied Soil Ecology, 2026)

From cropland to alpine meadows: Earthworm diversity in agroecosystems across Austria - Marion Mittmannsgruber; Dmytro Monoshyn; Edith Gruber; Elisabeth Wiedenegger; Csaba Csuzdi; Kathrin Pascher; Erich Inselsbacher; Rajasekaran Murugan; Johann G. Zaller (Agriculture, Ecosystems & Environment, 2026)

Earthworm and soil microarthropod abundances affected by agricultural land use and soil properties - Marion Mittmannsgruber; Dmytro Monoshyn; Claudia Slawiczek; Kian A. Taheri; Fee Wollenweber; Beate Meißner; Kathrin Pascher; Edith Gruber; Elisabeth Wiedenegger; Erich Inselsbacher; Rajasekaran Murugan; Johann G. Zaller (Pedobiologia, 2025)

Unexpected air pollutants with potential human health hazards: Nitrification inhibitors, biocides, and persistent organic substances - Johann G. Zaller; Maren Kruse-Plaß; Ulrich Schlechtriemen; Edith Gruber; Maria Peer; Imran Nadeem; Herbert Formayer; Hans-Peter Hutter; Lukas Landler (Science of The Total Environment, 2023)

Commercial glyphosate-based herbicides effects on springtails (Collembola) differ from those of their respective active ingredients and vary with soil organic matter content - Michael Maderthaner; Maureen Weber; Eszter Takács; Mária Mörtl; Friedrich Leisch; Jörg Römbke; Pascal Querner; Ronnie Walcher; Edith Gruber; András Székács; Johann G. Zaller (Environmental Science and Pollution Research, 2020)
Glyphosate-based herbicides (GBH) are currently the most widely used agrochemicals for weed control. Environmental risk assessments (ERA) on nontarget organisms mostly consider the active ingredients (AIs) of these herbicides, while much less is known on effects of commercial GBH formulations that are actually applied in the field. Moreover, it is largely unknown to what extent different soil characteristics alter potential side effects of herbicides. We conducted a greenhouse experiment growing a model weed population of Amaranthus retroflexus in arable field soil with either 3.0 or 4.1% soil organic matter (SOM) content and treated these weeds either with GBHs (Roundup LB Plus, Touchdown Quattro, Roundup PowerFlex) or their respective AIs (isopropylammonium, diammonium or potassium salts of glyphosate) at recommended dosages. Control pots were mechanically weeded. Nontarget effects were assessed on the surface activity of the springtail species Sminthurinus niger (pitfall trapping) and litter decomposition in the soil (teabag approach). Both GBHs and AIs increased the surface activity of springtails compared to control pots; springtail activity was higher under GBHs than under corresponding AIs. Stimulation of springtail activity was much higher in soil with higher SOM content than with low SOM content (significant treatment x SOM interaction). Litter decomposition was unaffected by GBHs, AIs or SOM levels. We suggest that ERAs for pesticides should be performed with actually applied herbicides rather than only on AIs and should also consider influences of different soil properties.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Effects of Glyphosate-, Glufosinate- and Flazasulfuron-Based Herbicides on Soil Microorganisms in a Vineyard - Karin Mandl; Clemens Cantelmo; Edith Gruber; Florian Faber; Barbara Friedrich; Johann G. Zaller (Bulletin of Environmental Contamination and Toxicology, 2018)

Herbicides in vineyards reduce grapevine root mycorrhization and alter soil microorganisms and the nutrient composition in grapevine roots, leaves, xylem sap and grape juice - Johann G. Zaller; Clemens Cantelmo; Gabriel Dos Santos; Sandrina Muther; Edith Gruber; Paul Pallua; Karin Mandl; Barbara Friedrich; Ingrid Hofstetter; Bernhard Schmuckenschlager; Florian Faber (Environmental Science and Pollution Research, 2018)

Isolation of a chymotrypsinogen B-like enzyme from the archaeon Natronomonas pharaonis and other halobacteria - H. Stan-Lotter; Edith Doppler; Marina Jarosch; Christian Radax; Claudia Gruber; Ken-ichi Inatomi (Extremophiles, 1999)